Atmospheric Acoustic Remote Sensing - Bradley, Stuart (CRC Press, 2009)
Sonic Detection and Ranging (SODAR) systems and Radio Acoustic Sounding Systems (RASS) use sound waves to determine wind speed, wind direction, and turbulent character of the atmosphere. They are increasingly used for environmental and scientific applications such as analyzing ground-level pollution dispersion and monitoring conditions affecting wind energy generation. However, until now there have been no reliable references on SODAR and RASS for practitioners in the field as well as non-experts who wish to understand and implement this technology to their own applications.